Will a government find it financially easier to neutralize a looming protest if more groups are involved? - Oded Stark; Ewa Zawojska (University of Tübingen, Faculty of Economics and Social Sciences, 2016)
We study a policy response to an increase in post-merger social stress. If a merger of groups of people is viewed as a revision of their social space, then the merger alters people's comparators and increases social stress: the social stress of a merged population is greater than the sum of the levels of social stress of the constituent populations when apart. We use social stress as a proxy measure for looming social protest. As a response to the post-merger increase in social stress, we consider a policy aimed at reversing the negative effect of the merger by bringing the social stress of the merged population back to the sum of the premerger levels of social stress of the constituent populations when apart. We present, in the form of an algorithm, a cost-effective policy response which is publicly financed and does not reduce the incomes of the members of the merged population. We then compare the financial cost of implementing such a policy when the merger involves more or fewer groups. We show that the cost may fall as the number of merging groups rises.
urn:nbn:de:bsz:21-dspace-719371
Keywords: D04; D63; F55; H53; P51; 330; Merger of populations; Revision of social space; Aggregate relative deprivation; Social stress; A cost-effective policy response